21-Epi-taichunamide D and (±)-versicaline A, three unusual alkaloids from the endophytic Aspergillus versicolor F210. Issue 33 (13th August 2020) - Li, Huaqiang; Xu, Qianqian; Sun, Weiguang; Zhang, Runge; Wang, Jianping; Lai, Yongji; Hu, Zhengxi; Zhang, Yonghui
Graphical abstract: Highlights: Three unusual alkaloids were isolated from Aspergillus versicolor F210. 21- Epi -taichunamide D features a rare methylsulfonyl unit. (±)- Versicalin A exist as two pairs of keto-enol tautomers. (± )-Versicalin A exhibited moderate cytotoxicity against HL-60 cells. Abstract: Three new alkaloids, 21- epi -taichunamide D (1 ) and (± )-versicalin A ((± )-6 ), along with four known analogues (2 –5 ) were isolated from the endophytic Aspergillus versicolor F210, which harbored in the bulbs of Lycoris radiata . Structurally, compound 1 is the third natural indole alkaloid with a rare methylsulfonyl unit, and (± )-6 existing as two pairs of keto-enol tautomers ((+)-6a/ (+)-6b and (−)-6a/ (−)-6b, respectively), represent the first naturally occurring alkaloids with a rare 2, 3-dihydro-1 H -isoindol-1-one unit fused to a tautomeric diisopentenyl cyclohexenone unit. The absolute structures of 1 and (± )-6 were characterized by extensive analyses of spectroscopic data, comparison of the electronic circular dichroic (ECD) data, and single-crystal X-ray diffraction analysis, respectively. Compound 6 exhibited moderate cytotoxicity against HL-60 cells with an IC50 value of 5.6 μ M.